2018
DOI: 10.1016/j.drugalcdep.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing JUUL-related posts on Twitter

Abstract: Background: As vaping rapidly becomes more prevalent, social media data can be harnessed to capture individuals’ discussions of e-cigarette products quickly. The JUUL vaporizer is the latest advancement in e-cigarette technology, which delivers nicotine to the user from a device that is the size and shape of a thumb drive. Despite JUUL’s growing popularity, little research has been conducted on JUUL. Here we utilized Twitter data to determine the public’s early experiences with JUUL describing topics of posts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
107
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 19 publications
15
107
1
1
Order By: Relevance
“…Research shows individuals are more likely to share information about ecigarettes on social media if they are current users or have favorable opinions about vaping products (Emery, Vera, Huang, & Szczypka, 2014). Moreover, studies suggest individuals connected through social media may bond through online e-cigarette discussions, which could normalize e-cigarette use (Allem et al, 2018).…”
mentioning
confidence: 99%
“…Research shows individuals are more likely to share information about ecigarettes on social media if they are current users or have favorable opinions about vaping products (Emery, Vera, Huang, & Szczypka, 2014). Moreover, studies suggest individuals connected through social media may bond through online e-cigarette discussions, which could normalize e-cigarette use (Allem et al, 2018).…”
mentioning
confidence: 99%
“…Small battery size was identified as preferable, possibly considered sleeker, pointing to another design feature that could be regulated in the future. Prior research has documented that the overall size and sleek shape of e-cigarette devices (especially JUUL) were discussed features on social media including among youth 22,43 . Modular and compatible e-cigarette designs may facilitate transition across different types of devices (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Publicly accessible data from social media platforms (like Twitter and Instagram) have been used in prior research to capture and document the environmental context and appeal of e-cigarette use [20][21][22] . Such platforms may also be able to provide insight to the product design features of e-cigarettes that increase their appeal to current and potential users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of Juul use among young people is partly facilitated by its resemblance to a USB-drive, high level of nicotine, and emissions that are hard to see [3]. Several recent studies explore and characterize social media posts related to Juul use and dependency [4,5,6,7]; however, to our knowledge, none are designed for the purpose of predictive modeling of Juul usage by consumers based on their social media feeds. In this first of its kind study, using self-reported survey answers as ground truth, we explore the potential for using publicly available historical Twitter data, including Twitter messages (tweets) and friend and follower networks, to predict an individual's past 30-day use of Juul.…”
Section: Introductionmentioning
confidence: 99%